Rural Social Work Practice in Turkey - Uzunaslan, Serif (Routledge Journals, Taylor & Francis Ltd, 2025)
Rural social work continues to grow in importance as a unique field of practice with unique opportunities and challenges. This qualitative research explores explore different aspects of rural social work in Turkey. To this end, the study explores social work practice in rural communities in depth, recognizing the distinctive contexts and characteristics that influence service delivery. In-depth interviews were conducted with rural social workers (n = 30) with significant knowledge and experience in addressing the social work needs of rural communities. Participants were selected through purposive sampling to ensure a broad representation of expertise and geographic diversity. Thematic analysis was used to identify recurring themes and patterns in the participants' responses. The findings support previous studies that have argued that rural social work is a distinct field of practice. At the same time, the study shows that social work practices are shaped in an urban-centered manner, and local culture is ignored. The study concludes that rural social work should be integrated into graduate social work education, and even start during undergraduate education.
Keywords: Rural; social work; rural society; rurality; qualitative method